Semi-analytic off-axis X-ray source model. (23rd October 2017) - Shamshad, M.; Anjomrouz, M.; Smithies, D.J.; Largeau, A.; Lu, G.; Atharifard, A.; Broeke, L. Vanden; Aamir, R.; Panta, R.K.; Walsh, M.F.; Goulter, B.P.; Healy, J.L.; et al.
Abstract: Spectral computed tomography (CT) systems are employed with energy-resolving photon counting detectors. Incorporation of a spectrally accurate x-ray beam model in image reconstruction helps to improve material identification and quantification by these systems. Using an inaccurate x-ray model in spectral reconstruction can lead to severe image artifacts, one of the extreme cases of this is the well-known beam-hardening artifacts. An often overlooked spectral feature of x-ray beams in spectral reconstruction models is the angular dependence of the spectrum with reference to the central beam axis. To address these factors, we have developed a parameterized semi-analytical x-ray source model in the diagnostic imaging range (30-120 kVp) by applying regression techniques to data obtained from Monte Carlo simulations (EGSnrc). This x-ray beam model is generalized to describe the off-axis spectral information within±17^o ±17 o alongθ θ (vertical direction), ±5^o ±5 o alongφ ϕ (horizontal direction) of the central axis, and can be parameterized for specific x-ray tube models. Comparisons of our model with those generated by SpekCalc, TOPAS, and IPEM78 at central axis show good agreement (within 2% % ). We have evaluated the model with experimental data collected with a small animal spectral scanner.